Trisomic Stages: Theater Hora and Jerome Bel’s Genetically Modified Theater - LEVINE, Debra (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
Disabled Theater (2012) is choreographer Jérôme Bel’s performance-based investigation into “how theater is modified when it is done by actors with a learning disability and what theater does to actors with a learning disability” (Bel) By proliferating the codes of theatricality Disabled Theater succeeds in intertwining critical reflection and intensive affect. Audiences become uncomfortably aware of how the seemingly mimetic failure of the performers and their child-like vulnerability produce the quality of “presence” that is currently fetishized in live performance. Alongside Bel and Theater Hora, this paper asks whether Disabled Theater’s production of a trisomic stage and its capacity as a critical affect mechanism might expand theater’s disciplinary and disciplining genetic composition in order to homeopathically relieve the art form of its complicity in the project of social normalization.